Muscle Electrical Impedance Properties and Activation Alteration After Functional Electrical Stimulation-Assisted Cycling Training for Chronic Stroke Survivors: A Longitudinal Pilot Study - Hu, Chengpeng; Wang, Tong; Leung, Kenry W. C.; Li, Le; Tong, Raymond Kai-Yu (Frontiers in Neurology, 2021)
Electrical impedance myography (EIM) is a sensitive assessment for neuromuscular diseases to detect muscle inherent properties whereas surface electromyography (sEMG) is a common technique for monitoring muscle activation. However, the application of EIM in detecting training effects on stroke survivors is relevantly few. This study aimed to evaluate the muscle inherent properties and muscle activation alteration after functional electrical stimulation (FES) assisted cycling training for chronic stroke survivors. Fifteen people with chronic stroke were recruited for 20 sessions of FES assisted cycling training (40min/session, 3-5 sessions/week). The periodically stimulated and assessed muscle groups were quadriceps (QC), tibialis anterior (TA), hamstrings (HS) and medial head of gastrocnemius (MG) on the affected lower extremity. EIM parameters (resistance (R), reactance (X) and phase angle(θ), and anisotropy ration (AR)), clinical scales (Fugl-Meyer Lower Extremity (FMALE), Berg Balance Scale (BBS) and 6 minutes’ walking test (6MWT)) and sEMG parameters (including root-mean square (RMS) and co-contraction index (CI) value) were collected and computed before and after training. Linear correlation analysis was conducted between EIM and clinical scales as well as between sEMG and clinical scales. The results showed that motor function of lower extremity, balance, and walking performance of subjects improved after the training. After training, θ value of TA (P=0.014) and MG (P=0.017) significantly increased, and AR of X (P=0.004) value and AR of θ value (P=0.041) significantly increased on TA. The RMS value of TA decreased (P=0.022) and significant reduction of CI was revealed on TA/MG muscle pair (P<0.001). Significant correlation was found between EIM and clinical assessments (AR of X value of TA and FMA-LE: r = 0.54, P = 0.046; X value of TA and BBS score: 0.628, P = 0.016), and between sEMG and clinical scores (RMS of TA and BBS score: r = -0.582, P = 0.029). This study demonstrated that FES assisted cycling training improved lower limb function by developing coordinated muscle activation and facilitating orderly myofibers arrangement. The current study also indicated that EIM can jointly evaluate lower extremity function alteration with sEMG after rehabilitation training.